The effect of a transforaminal epidural injection in patients with lumbar disc herniation is not correlated with the presence of type II modic changes - E.J.A. Verheijen; N.R.E. van der Vlist; E.C. Bartels; O.B.H.A.M. van Haagen; C.L.A. Vleggeert-Lankamp (Brain and Spine)
Introduction: Transforaminal epidural steroid injections (TEI) have been suggested to alleviate symptoms in patients with lumbar disc herniation (LDH) through its anti-inflammatory effect. However, treatment effect varies among patients and reliable predictors are lacking. Modic changes (MC) are also associated with inflammatory processes and, therefore, we hypothesize that MC may be correlated with outcome after TEI. Research question: To investigate the correlation between the presence of MC at the level of LDH and the effect of TEI. Material and methods: Patients with unilateral lumbar radiculopathy secondary to LDH undergoing TEI were included. MC was graded by two independent assessors. Outcome measures included leg pain, back pain, disability and patient-received recovery at baseline, 30 min, 2 weeks and 6 weeks after treatment. Multivariate analysis was performed for all outcomes and for dichotomized scores using a cutoff of ≥30% improvement. A p-value of ≤0.05 was considered statistically significant. Results: A total of 88 patients were included of whom 52.3% demonstrated MC. The vast majority was classified as type II (94%). The presence of MC was not correlated with any outcome measure when correcting for age, gender, duration of symptoms and the use of analgesics, nor for dichotomized scores. Discussion and conclusion: The findings indicate that type II MC is not associated with outcome within six weeks after TEI. Therefore, type II MC cannot be used as a predictor for TEI outcome. Future studies should include longer follow-up and investigate the correlation between the type of MC and the effect of TEI.